What has happened to replacement rates? - Callan, Tim; Nolan, Brian; O'Donoghue, Cathal (Economic & Social Studies, 1996)
This paper compares different approaches to measuring changes in replacement rates in Ireland over time. Results based on microsimulation modelling suggest that the average replacement rate facing unemployed persons was roughly constant between 1987 and 1994, with a small rise for those on Unemployment Assistance offset by a decline for those on Unemployment Benefit. The mean predicted wage facing the unemployed is about two-thirds of the average industrial wage. Time-series constructed using average expenditure per unemployment compensation recipient and average earnings do not accurately reflect changes in mean replacement rates. In addition to providing a better measure of the overall trend in replacement rates, microsimulation modelling provides a picture of their distribution, showing that the incidence of cash replacement rates over 80 per cent fell between 1987 and 1994 but the numbers facing rates between 70 and 80 per cent rose.
Keywords: Replacement rates; Unemployment; Ireland; Labour market